Roles of immune cell metabolism in rheumatoid arthritis - Xie, Rui; Chen, Zeping; Deng, Shufang; Jiang, Xiaofeng; Feng, Yue; Zhao, Wei (Frontiers in Immunology, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent synovial inflammation and progressive joint destruction. Recent advances reveal that immune cell metabolism plays a pivotal role in shaping RA pathogenesis. Aberrant glycolysis, lipid reprogramming, and amino acid catabolism drive functional alterations in T cells, B cells, macrophages, neutrophils, and fibroblast-like synoviocytes (FLSs), promoting inflammatory cytokine production, angiogenesis, and autoantibody generation. Key metabolites—such as lactate, succinate, and glutamine—not only serve as energy substrates but also act as immunomodulatory signals via the HIF-1α, PI3K/AKT/mTOR, and NF-κB pathways, exacerbating immune dysfunction and tissue damage. The plasticity of metabolic states contributes to Treg/Th17 imbalance, proinflammatory macrophage polarization, and FLS hyperactivation. Targeting these metabolic checkpoints has shown promise in restoring immune tolerance and alleviating disease severity. This review summarizes the complex interplay between immune cell metabolism and RA pathophysiology, highlights mechanistic insights into immunometabolic reprogramming, and discusses emerging metabolic interventions that may complement conventional RA therapies.